Philippine and South African Experiences on Folk Literature Research: Relevance, Gains, and Challenges - Makgabo, Connie; Quintero, Genevieve J (Universitas Pendidikan Mandalika, 2024)
Folkloric studies have accelerated in the Philippines and South Africa because the Academe acknowledged the urgency to collect, preserve, and publish the oral traditions of indigenous communities. Oral traditions embody the history, values, and world views of these indigenous cultures, which need to be preserved for posterity. This paper discusses the relevance, gains, and challenges in conducting folklore research in the Philippines and South Africa, which share similarities, including their colonial pasts and number of indigenous communities. The paper contemplates the relevance of folklore research outputs in different fields thereby contributing to the discourse on the value of folklore research. This qualitative study uses textual analysis to focus on insights related to folklore research, using secondary data including journal articles, book publications, and textual references. The study reveals that although there is extensive research in the field of folklore in both countries, there remain gaps that need to be filled, such as the collection, preservation, and recognition of representative folklore from other regions and cultural communities. South Africa, for instance, has 12 official languages, and the Philippines has 110 ethnolinguistic groups. There are still languages and indigenous oral traditions that are developing, and folk literature that needs to be recorded, preserved, and published. These oral traditions/folk literature play an important role in revealing people’s cultural identities and preserving heritage, which is imperative in nation-building. The findings highlight the importance of continuing research about folklore and the need to preserve indigenous knowledge systems When written down and published, folklore becomes tangible and preserved for posterity, providing present and future generations the opportunity to learn, understand, and appreciate their cultural legacy.